Impact of climate change on trans-arctic navigation; a Northern Sea Route case study - Haddaden, N.H.M. (author) (2010)
This thesis reviews Arctic development, and industrial responses to changing climate-driven, geospatial, and economic environments. First, the optimization of trans-arctic navigation was addressed in light of the global warming impact on Arctic sea ice. In this regard, a central consideration was given to the Northern Sea Route (NSR), such that its history, characteristics and future interests were addressed. Following, an environmental management scheme was developed in line with today’s sustainable development principles. Advanced mitigation measures were proposed for the proposed development, in consistence with the most recent recommendations of international regulations. Finally, the thesis quantitatively scrutinized the comparative environmental profiles of NSR passage and Suez Canal transit. Environmental mapping was used for this purpose such that carbon foortprint estimates formed the basis for comparing generated emissions as a result of shipping activities of the case study in question. The synergy between fuel consumption, energy consumption and generated emissions was reflected in the model. Further, the role of slow steaming was highlighted in terms of reducing emissions for all considered cases. The study also recommended several areas of research in respect to the investigated impacts. In conclusion, the thesis notes that the NSR, despite its ice-infested waters, presents the most environmentally feasible routing out of the presented alternatives. A question worth investigating then: how will trans-arctic navigation in an ice-free Arctic interact with the existing impacts of climate change? CoMEM - Coastal and Marine Engineering and Management Hydraulic Engineering Civil Engineering and Geosciences